2021
DOI: 10.1021/acs.jmedchem.1c01010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fibroblast Activation Protein-α Expression: Focus on Intracellular Protein Interactions

Abstract: The prolyl-specific peptidase fibroblast activation protein-α (FAP-α) is expressed at very low or undetectable levels in nondiseased human tissues but is selectively induced in activated (myo)fibroblasts at sites of tissue remodeling in fibrogenic processes. In normal regenerative processes involving transient fibrosis FAP-α + (myo)fibroblasts disappear from injured tissues, replaced by cells with a normal FAP-α − phenotype. In chronic uncontrolled pathological fibrosis FAPα + (myo)fibroblasts permanently repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 151 publications
0
7
0
Order By: Relevance
“…Cancer-associated fibroblasts (CAFs) are central components of the tumor microenvironment (TME) and play crucial roles in tumor development, immune suppression, and cancer invasion. A notable biomarker highly expressed in CAFs is the fibroblast activation protein (FAP), a type II membrane-bound glycoprotein. FAP is upregulated in numerous epithelial carcinomas, wound healing, arthritis, atherosclerotic plaques, and fibrosis, with little expression in normal tissues. Thus, it is considered a promising target for cancer diagnosis and therapy. …”
Section: Introductionmentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs) are central components of the tumor microenvironment (TME) and play crucial roles in tumor development, immune suppression, and cancer invasion. A notable biomarker highly expressed in CAFs is the fibroblast activation protein (FAP), a type II membrane-bound glycoprotein. FAP is upregulated in numerous epithelial carcinomas, wound healing, arthritis, atherosclerotic plaques, and fibrosis, with little expression in normal tissues. Thus, it is considered a promising target for cancer diagnosis and therapy. …”
Section: Introductionmentioning
confidence: 99%
“…However, normal tissues and healthy activated fibroblasts also express FAP during wound healing, such as the activation of myofibroblasts post-myocardial infarction. While both LRRC15 and FAP have been shown to be upregulated by TGFβ (30), recent studies revealed a unique subset of TGFβ-driven CAFs that express LRRC15 and are negative for FAP expression (4, 8), and that these LRRC15+ CAFs are associated with CD8+ T-cell exclusion (8). During our therapeutic studies, a notable observation emerged: LRRC15+ tumors exhibited a concurrent reduction in both growth and the TGFβ–LRRC15 gene signature upon exposure to RIT.…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulators of FAPα expression include estrogens and activators of PTEN protein [86,87]. Importantly, the FAPα promoter region is known to contain binding sites for several transcription factors-AREB6, ITF-2, Meis-1, PPAR-gamma1, PPAR-gamma2, and Tal-1beta [88].…”
Section: Factors Influencing Fapα Expressionmentioning
confidence: 99%